Polynomial based iteration methods for symmetric linear systems - Fischer, Bernd (Wiley-Teubner series, advances in numerical mathematics., 1996)
This book provides a concise introduction to computational methods for solving large linear systems of equations. It is the only textbook that treats iteration methods for symmetric linear systems from a polynomial point of view. This particular feature enables readers to understand the convergence behavior and subtle differences of the various schemes, which are useful tools for the design of powerful preconditioners.